A novel feeding platform design for behavioral research on wild Tanimbar corellas (Cacatua goffiniana) - O’Hara, Mark; Auersperg, Alice M. I.; Prawiradilaga, Dewi M.; Huber, Ludwig; Mioduszewska, Berenika (Frontiers in Ecology and Evolution, 2024)
The study of animal behaviour and cognition would not be complete without investigations of wild, free-ranging individuals in their natural environment. However, direct observations of species living in dense habitats can be challenging, leading many studies to focus on attracting target species to pre-selected, monitored locations baited with food. So far, researchers have rarely applied this approach to studying wild psittacines – an avian group of high scientific interest due to their advanced cognitive skills and conservation threats. We developed hoistable feeding platforms and tested their suitability for reliably attracting groups of wild Tanimbar corellas (hereafter: Goffins), opportunistic feeding generalists well-known for their advanced cognitive skills. To this end, we recorded the visitation rates of free-ranging groups at feeding platforms temporarily baited with dry corn. Moreover, we investigated the effects of several weather-related measures, the temporal distribution of foraging activity, and the effect of conspecific contact calls (playback stimulus). The results indicate that Goffins accepted the feeding platforms and reliably aggregated within their natural daily foraging bouts. While group size during visitation bouts depended on rainfall and resource abundance, platforms were still regularly visited by fewer, possibly locally residing individuals. These results provide the first systematic investigation of the temporal distribution and social dynamics of foraging bouts in wild Goffins. This study presents a novel method for reliably attracting wild opportunistic feeding generalist psittacines to a standardised, monitored location. It provides a suitable approach for observing foraging aggregations and, in the future, testing the problem-solving abilities of free-ranging Goffins in their natural habitat.